False-Positive Clostridium difficile in Negative-Control Reactions Peak and Then Decrease with Repetitive Refrigeration of Immunoassay. (11th September 2014) - Rodriguez-Palacios, Alexander; Stämpfli, Henry R.; Chang, Yung-Fu
Abstract : Aberrant false-positive reactions in negative-controls during ELISA testing for Clostridium difficile indicated the potential for false-diagnoses. Experiments with 96-well products showed a maximum peak of false-positive immunoassay reactions with the provided negative-control reagents after 5 refrigeration-to-room temperature cycles (P < 0.001 ), decreasing thereafter with additional refrigeration cycles. Because repetitive refrigeration causes a peak of false-positives, the use of single negative-controls per ELISA run might be insufficient to monitor aberrant preanalytical false-positives if immunoassays are subject to repetitive refrigeration.